Implementation of ethnosains in science learning in madrasah ibtidaiyah - Aisyah, Nur; Khotimah, Husnul (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to analyze and describe science learning based on ethnoscience at MI Darul Ulum Paiton. Ethnoscience learning is the integration of local cultural values ​​into the learning process, especially science subjects.This research uses a descriptive qualitative approach. The research subjects were students of MI Darul Ulum Class IV. The research results show that ethnoscience-based science learning at MI Darul Ulum is carried out in three stages, namely planning, implementation, and evaluation. Planning is carried out routinely at the beginning of the semester by the class teacher. Implementation of learning emphasizes contextual learning. Evaluation is carried out authentically to measure student performance. In addition to measuring the affective, cognitive, and psychomotor domains, morals are the main consideration in the evaluation process.The purpose of this study was to analyze and describe science learning based on ethnoscience at MI Darul Ulum Paiton. Ethnoscience learning is the integration of local cultural values ​​into the learning process, especially science subjects.This research uses a descriptive qualitative approach. The research subjects were students of MI Darul Ulum Class IV. The research results show that ethnoscience-based science learning at MI Darul Ulum is carried out in three stages, namely planning, implementation, and evaluation. Planning is carried out routinely at the beginning of the semester by the class teacher. Implementation of learning emphasizes contextual learning. Evaluation is carried out authentically to measure student performance. In addition to measuring the affective, cognitive, and psychomotor domains, morals are the main consideration in the evaluation process.The purpose of this study was to analyze and describe science learning based on ethnoscience at MI Darul Ulum Paiton. Ethnoscience learning is the integration of local cultural values ​​into the learning process, especially science subjects.This research uses a descriptive qualitative approach. The research subjects were students of MI Darul Ulum Class IV. The research results show that ethnoscience-based science learning at MI Darul Ulum is carried out in three stages, namely planning, implementation, and evaluation. Planning is carried out routinely at the beginning of the semester by the class teacher. Implementation of learning emphasizes contextual learning. Evaluation is carried out authentically to measure student performance. In addition to measuring the affective, cognitive, and psychomotor domains, morals are the main consideration in the evaluation process.The purpose of this study was to analyze and describe science learning based on ethnoscience at MI Darul Ulum Paiton. Ethnoscience learning is the integration of local cultural values ​​into the learning process, especially science subjects.This research uses a descriptive qualitative approach. The research subjects were students of MI Darul Ulum Class IV. The research results show that ethnoscience-based science learning at MI Darul Ulum is carried out in three stages, namely planning, implementation, and evaluation. Planning is carried out routinely at the beginning of the semester by the class teacher. Implementation of learning emphasizes contextual learning. Evaluation is carried out authentically to measure student performance. In addition to measuring the affective, cognitive, and psychomotor domains, morals are the main consideration in the evaluation process.The purpose of this study was to analyze and describe science learning based on ethnoscience at MI Darul Ulum Paiton. Ethnoscience learning is the integration of local cultural values ​​into the learning process, especially science subjects.This research uses a descriptive qualitative approach. The research subjects were students of MI Darul Ulum Class IV. The research results show that ethnoscience-based science learning at MI Darul Ulum is carried out in three stages, namely planning, implementation, and evaluation. Planning is carried out routinely at the beginning of the semester by the class teacher. Implementation of learning emphasizes contextual learning. Evaluation is carried out authentically to measure student performance. In addition to measuring the affective, cognitive, and psychomotor domains, morals are the main consideration in the evaluation process.The purpose of this study was to analyze and describe science learning based on ethnoscience at MI Darul Ulum Paiton. Ethnoscience learning is the integration of local cultural values ​​into the learning process, especially science subjects.This research uses a descriptive qualitative approach. The research subjects were students of MI Darul Ulum Class IV. The research results show that ethnoscience-based science learning at MI Darul Ulum is carried out in three stages, namely planning, implementation, and evaluation. Planning is carried out routinely at the beginning of the semester by the class teacher. Implementation of learning emphasizes contextual learning. Evaluation is carried out authentically to measure student performance. In addition to measuring the affective, cognitive, and psychomotor domains, morals are the main consideration in the evaluation process.